VD_FINDINFO HC / 2019 / 104 vom 4. März 2019 - VD Tribunal cantonal (2019)
OBLIGATION D'ENTRETIEN, DIVORCE, REVENU HYPOTHÉTIQUE, PRÉVOYANCE PROFESSIONNELLE, CONCUBINAGE | 125 al. 1 CC, 317 al. 1 CPC (CH)